2009
DOI: 10.3171/2009.6.peds08450
|View full text |Cite
|
Sign up to set email alerts
|

Management of osteoblastoma and osteoid osteoma of the spine in childhood

Abstract: Object Osteoid osteomas and osteoblastoma of the spine are rare lesions in childhood, and management strategies have changed. The authors reviewed their recent experience with these 2 types of lesions to elucidate current treatment modalities and outcomes. Methods Case records and radiographic images from all cases of osteoid osteoma and osteoblastoma diagnosed between 1993 and 2008 were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 12 publications
3
54
1
Order By: Relevance
“…Plain radiography is the most common radiological choice and is thought to have great value for diagnosing spinal OBLs [17][18][19][20]. However in our study, normal images were found in half of the patients with CO and onefourth of cases with AO, which might cause a high number of misdiagnoses if it were the only diagnostic tool used.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Plain radiography is the most common radiological choice and is thought to have great value for diagnosing spinal OBLs [17][18][19][20]. However in our study, normal images were found in half of the patients with CO and onefourth of cases with AO, which might cause a high number of misdiagnoses if it were the only diagnostic tool used.…”
Section: Discussioncontrasting
confidence: 60%
“…Although few researchers believed that subtotal excision (curettage) or resection without a wide margin was sufficient for spinal OBL because of its benign nature and limited growth, the vast majority of experts held the view that radical surgical resection was the best possible treatment [2,4,6,8,17,[24][25][26][27][28]. In our series, total excision had a much better outcome than subtotal excision ?…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…3,8 Ninety percent of cases occur during the first 2 decades of life, with a peak incidence between the ages of 10 and 20 years. 1,9,17 There is a male predominance (male to female ratio of 1.43-4.7:1).…”
Section: Discussionmentioning
confidence: 99%
“…1,16 These lesions are one-fourth to one-tenth as common as osteoid osteomas from which they can be difficult to differentiate clinically. 3,8 Ninety percent of cases occur during the first 2 decades of life, with a peak incidence between the ages of 10 and 20 years. 1,9,17 There is a male predominance (male to female ratio of 1.43-4.7:1).…”
Section: Discussionmentioning
confidence: 99%